Comparison of bacterial load of enteroaggregative Escherichia coli (EAEC) by real-time PCR (qPCR) in children under 2 years of age with or without diarrhea from a peri-urban area of Lima, Peru. - Durand, David (2019)
Introduction: Enteroagregative Escherichia coli (EAEC) is a group of enteric pathogens that cause acute and persistent diarrhea among children, in patients infected with human immunodeficiency virus, which causes traveler's diarrhea and are associated with important outbreaks that have caused death. AIM: The aims of this study were to quantify and compare the bacterial load of stool samples from children under 2 years of age with and without diarrhea in a periurban community in Lima, Peru. Materials and methods: We randomly selected 165 stool samples (80 from diarrhea and 85 from asymptomatic patients) that previously were identified as EAEC for the presence of aggR plasmidic gene by Real Time-PCR for Diagnostic of Diarrheagenic E. coli (DEC) from bacteria isolated of stool culture, placebocontrolled trial conducted in children living in the district of Independencia, Lima, Peru. This study was conclucted during 2008-2011 in 555 children between 12-18 months old, Cetyltrimethylammoniumbromide (CTAB) method was used to extract DNA from 200mg of infected stool, with diarrhea and control stool samples. The comparation of bacterial load was made by Wilcoxon test using STATA 12 and R studio program. Conclusions: In summary, EAEC load in fecal samples is higher in children with diarrhea than in healthy controls. This qPCR could be useful for studying the role of colonization versus symptomatic infection in children living in endemic areas were the isolation rate of this pathogen is similar in diarrhea and controls.